Optic flow influences perceived exertion during cycling - Parry, D.; Chinnasamy, C.; Micklewright, D. (Journal of Sport & Exercise Psychology, 2012)
The purpose of this study was to examine the relationship between athletes` perceptions of role ambiguity and two theoretically derived dimensions of coaching competency (i.e., game strategy and technique competencies). A total of 243 players from 26 teams representing various interdependent sports completed French versions of the Role Ambiguity Scale and the Coaching Competency Scale. Multilevel analyses supported the existence of relationships between the four dimensions of role ambiguity and the two dimensions of coaching competency at both individual and team levels. When the levels were considered jointly, athletes perceiving greater ambiguity in their role in both offensive and defensive contexts were more critical of their coach`s capacities to lead their team during competitions and to diagnose or formulate instructions during training sessions. The results also indicated that the dimension of scope of responsibilities was the main contributor to the relationship with coaching competency at an individual level, whereas role evaluation was the main contributor to this relationship at a group level. Findings are discussed in relation to the role episode model, the role ambiguity dimensions involved in the relationships according to the level of analysis considered, and the salience of ambiguity perceptions in the offensive context.